Analisis Faktor - Faktor yang Mempengaruhi Pertumbuhan Laba pada Industri Sub Sektor Makanan Dan Minuman di Bursa Efek Indonesia Periode 2015-2020 - Dwi Putri Isfaramadhani (Universitas Batanghari Jambi, 2021)
This research aims, to analyze the factors assessed from Working Capital to Total Asset, Current Liabilities to Inventory, Operating Income to Total Liabilities, Total Assets Turnover, Net Profit Margin and Gros Profit Margin simultaneously or partial influence profit growth in the sub industry food and beverage on the Indonesia Stock Exchange for the period 2015-2020. The research methodology is descriptive and quantitative analysis methods. Data used is secondary data. The population become object in this research is the sub industry food and beverage on the Indonesia Stock Exchange period 2015-2020. Amount sample the used is three industry company and still stand up during period of perception and also publicized of year of 2015-2020 by Indonesian Stock Exchange the analysis multiple regression, hypotesis test so determinant coefficient F test and t test. The object of this research is food and beverage sub-sector industries during the period 2015 - 2020 consisting of 18 (eighteen) issuers. With respect to the method of sample withdrawal based on purposive sample and data limitations during the observation period, then that can be used as a sample in this study there are 9 (Nine) issuers. The sample consisted of PT Wilmar Cahaya Indonesia,Tbk (CEKA), PT Delta Djakarta,Tbk (DLTA), PT Indofood Sukses Makmur,Tbk (INDF), PT Nippon Indosari Corpindo,Tbk (ROTI), PT Sekar Laut,Tbk (SKLT), PT Ultra Jaya Milk Industri &Trading,Tbk (ULTJ), PT Moyora Indah,Tbk (MYOR), PT Akasha Wira International, Tbk (ADES), PT Multi Bintang Indonesia, Tbk (MLBI) Research results model of regression equation is Y = 0,374 + 0,907 X1 + 0,179 X2 - 0,165 X3 + 0,258 X4 + 0,455 X5 + 0,074 X6 + e. F test result, it is known that idependent variabel simultaneously significant effect on profit growth. Fcount larger than Ftable (6,580 > 2,30) or comparing the significant level of 0.05 then (0.000 < 0.05) then Ho is rejected and Ha accepted. From the results t test on independent variabel is working capital to total asset and net profit margin in partial effect to profit growt to the value of tcount > ttable. Conclusion is inflation, independent variabel simultaneousl significant effect on profit growth.. While partially working capital to total asset and net profit margin in partial effect to profit growth